Associations between discrimination and substance use among college students in the United States from 2015 to 2019. (February 2022) - Qeadan, Fares; Azagba, Sunday; Barbeau, William A.; Gu, Lily Y.; Mensah, Nana A.; Komaromy, Miriam; English, Kevin; Madden, Erin F.
Highlights: Discrimination has significant associations with many kinds of substance use. However, the magnitude of associations varies by substance type. Discrimination is associated with higher odds of inhalants and methamphetamine use. Associations between discrimination and substance use vary by race, age, and gender. Associations between discrimination and substance use vary by sexual orientation. Abstract: Discrimination has been associated with adverse health behaviors and outcomes, including substance use. Higher rates of substance use are reported among some marginalized groups, such as lesbian, gay, and bisexual populations, and have been partially attributed to discrimination. This study uses 2015–2019 National College Health Assessment data to determine whether college students reporting discrimination due to sexual orientation, race/ethnicity, gender, or age report greater substance use than their peers who do not report such experiences. Additionally, we assess exploratory questions regarding whether substance choices differ among students who reported facing discrimination. Over time, about 8.0% of students reported experiencing discrimination in the past year. After applying inverse probability treatment weights (IPTWs), exposure to discrimination was associated with an excess of 44 cases of marijuana use per 1000 students, an excess of 39 cases of alcohol use per 1000 students, and an excess of 11 cases of prescription painkiller use per 1000 students. Multivariable logistic regression models with IPTW demonstrated that students who experienced discrimination were more than twice as likely to use inhalants and methamphetamine. These students were also significantly more likely to use other drugs, including opiates, non-prescribed painkillers, marijuana, alcohol, hallucinogens, cocaine, and cigarettes; however, the differences with peers were smaller in magnitude. Students who experienced discrimination did not differ from peers who reported non-prescribed antidepressants use and were significantly less likely to use e-cigarettes and smokeless tobacco. Associations between discrimination and substance use vary by race, gender, sexual orientation, and age. These findings indicate that discrimination has significant associations with many kinds of substance use; however, the magnitude varies by substance type. More institutional efforts to address sources of discrimination affecting college students are needed.